2021
DOI: 10.1111/jsr.13350
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic alternating pattern in obstructive sleep apnea: A preliminary study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
(54 reference statements)
0
27
0
Order By: Relevance
“…One of the important unresolved questions in the sleep medicine is whether its second most prevalent sleep disorder, OSA, may indeed also lead to inflammatory responses in the brain (5,6,42,43). This is of particular note as neuroinflammation has been argued to act as a shared archetypal mechanism in the pathogenesis of Alzheimer's disorder (AD), depression and several other major neurologic and psychiatric disorders with which OSA appears to share a complex bidirectional link (6,42,44).…”
Section: Neuroinflammation In Osamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important unresolved questions in the sleep medicine is whether its second most prevalent sleep disorder, OSA, may indeed also lead to inflammatory responses in the brain (5,6,42,43). This is of particular note as neuroinflammation has been argued to act as a shared archetypal mechanism in the pathogenesis of Alzheimer's disorder (AD), depression and several other major neurologic and psychiatric disorders with which OSA appears to share a complex bidirectional link (6,42,44).…”
Section: Neuroinflammation In Osamentioning
confidence: 99%
“…This is of particular note as neuroinflammation has been argued to act as a shared archetypal mechanism in the pathogenesis of Alzheimer's disorder (AD), depression and several other major neurologic and psychiatric disorders with which OSA appears to share a complex bidirectional link (6,42,44). Our group has long argued that accumulating data does suggest that neuroinflammatory process occurs in OSA, and that it drives specific structural and behavioural changes known to afflict some susceptible OSA patients (42,43,(45)(46)(47)(48)(49). More recently, we have been able to demonstrate that under OSA-like conditions in rodents, the neuroinflammatory response is indeed instigated in the forebrain and the septal nuclei regions, important cholinergic regions of the brain, with a later widespread and marked chronic component.…”
Section: Neuroinflammation In Osamentioning
confidence: 99%
“…A cyclic EEG alteration occurs during NREM, namely the cyclic alternating pattern (CAP), which reflects the microstructure of sleep and has a crucial role in establishing and maintaining sleep integrity (Terzano and Parrino, 2000;Smerieri et al, 2007). The CAP represents an adaptive state of persistent arousal instability that oscillates between higher levels of arousal and activation (stage A) and lower levels of arousal and deactivation (stage B) (Parrino et al, 2012;Gnoni et al, 2021). CAP and arousal are fundamental mechanisms of sleep regulation, with subtype A1 contributing to the accumulation and consolidation of deep slow-wave sleep (SWS), while subtypes A2 and A3 attenuate sleep and lead to episodes of REM sleep or arousal (Terzano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CAP and arousal are fundamental mechanisms of sleep regulation, with subtype A1 contributing to the accumulation and consolidation of deep slow-wave sleep (SWS), while subtypes A2 and A3 attenuate sleep and lead to episodes of REM sleep or arousal (Terzano et al, 2005). Studies have shown that CAP subtype A1 predominates in the mild OSA, while CAP subtypes A2 and A3 predominate in patients with moderate-to-severe OSA (Gnoni et al, 2021). In patients with mild OSA, CAP A1 subtypes may enhance sleep continuity, whereas, in moderate-to-severe OSA, there may be a loss of compensation of these sleep stabilization mechanisms and more invasive CAP fluctuations disrupting sleep circuits (Gnoni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation